ONGOING OPERATION AND PERSPECTIVES OF SIMPLE VLBI NETWORKS OF GEOSTATIONARY SATELLITES MONITORING - Kaliuzhnyi, M.; Zhang, Z.; Bushuev, F.; Shulga, O.; Bezrukovs, V.; Reznichenko, O.; Melnychuk, S.; Malynovskyi, Y. (Одеські астрономічні публікації, 2019)
The report is dedicated to introducing the operation and prospects of further development of simple VLBI networks which were created in Ukraine, Latvia, and China for monitoring the orbital information of geostationary satellites. The Ukrainian-Latvian network consists of five stations located in Mykolaiv, Kharkiv, Mukacheve, Ventspils, and Rivne, and it operates since 2015. The Chinese network consists of three stations lo- cated in Shanghai, Duyun, and Urumqi, and it formally carried out a network observation from June 2019. The networks have identical hardware and software. The main principle of the operation of the networks learned from the VLBI is correlation analysis of broadband noise- like signals of satellite television DVB-S, which are emitted by satellites and synchronously received by the stations of the networks. Single-frequency GPS receivers are used for the synchronizing of network stations. Time difference of arrival (TDOA) between the signals paths from the identical TV satellite to different stations is obtained via using corre- lation analysis. These values of TDOA are used to deter- mine orbital elements of the tracked satellites which are given in the report. Notably, the cost of one set of station equipment does not exceed 2000, and the current operat- ing costs are about 50 per day. The prospects of further development of the simple VLBI networks include a) the possibility of continuous independent non-invasive high-precision determination of the position of arbitrary active satellites (especially im- portant in the case of their co-location), b) the possibility to fully automate targeting and operation, c) the possibility of using accumulated observational data to solve scientific geophysical and astronomical tasks, d) relatively few funds necessary for the modernization and operation of the networks.